Mastering Counselling Theory - Colledge, Ray. (Basingstoke : Palgrave Macmillan, 2002)
This text provides comprehensive coverage of all the major concepts and ideas integral to the theory of counselling from behavioural to existential to psychodynamic studies.
Includes bibliographical references (p. 289-291) and index.
Keywords: Counseling; Society